Cardiovascular magnetic resonance reference ranges from the Healthy Hearts Consortium - Raisi-Estabragh, Zahra; Szabo, Liliana; McCracken, Celeste; Bülow, Robin; Aquaro, Giovanni Donato; André, Florian; Le, Thu-Thao; Suchá, Dominika; Condurache, Dorina-Gabriela; Salih, Ahmed M.; Chadalavada, Sucharitha; Aung, Nay; et al. (JACC Cardiovascular imaging, 2024)
Background - The absence of population-stratified cardiovascular magnetic resonance (CMR) reference ranges from large cohorts is a major shortcoming for clinical care. - Objectives - This paper provides age-, sex-, and ethnicity-specific CMR reference ranges for atrial and ventricular metrics from the Healthy Hearts Consortium, an international collaborative comprising 9,088 CMR studies from verified healthy individuals, covering the complete adult age spectrum across both sexes, and with the highest ethnic diversity reported to date. - Methods - CMR studies were analyzed using certified software with batch processing capability (cvi42, version 5.14 prototype, Circle Cardiovascular Imaging) by 2 expert readers. Three segmentation methods (smooth, papillary, anatomic) were used to contour the endocardial and epicardial borders of the ventricles and atria from long- and short-axis cine series. Clinically established ventricular and atrial metrics were extracted and stratified by age, sex, and ethnicity. Variations by segmentation method, scanner vendor, and magnet strength were examined. Reference ranges are reported as 95% prediction intervals. - Results - The sample included 4,452 (49.0%) men and 4,636 (51.0%) women with average age of 61.1 ± 12.9 years (range: 18-83 years). Among these, 7,424 (81.7%) were from White, 510 (5.6%) South Asian, 478 (5.3%) mixed/other, 341 (3.7%) Black, and 335 (3.7%) Chinese ethnicities. Images were acquired using 1.5-T (n = 8,779; 96.6%) and 3.0-T (n = 309; 3.4%) scanners from Siemens (n = 8,299; 91.3%), Philips (n = 498; 5.5%), and GE (n = 291, 3.2%). - Conclusions - This work represents a resource with healthy CMR-derived volumetric reference ranges ready for clinical implementation.
Online veröffentlicht: 10. April 2024, Artikelversion: 1. Juli 2024
Gesehen am 17.02.2025